Traditional management of Cactaceae: Cereus jamacaru DC as the native cactus most managed by rural communities in areas of Caatinga in Brazil - Lima-Nascimento, Ailza Maria de; Silva, José Severino Bento da; Casas, Alejandro; Lucena, Camilla Marques de; Lucena, Reinaldo Farias Paiva de (Ethnobotany Research and Applications, 2021)
Background: Studies on management practices reflect the quality of the actions regarding the managed resource by people and allow us to identify possible selective pressures over time. Methods: Was investigated how have been carrying out management practices using native cacti species in two communities. Data collection was through the ethnobotanical (semi-structured interviews) and morphometric approach (botanical measurements). It was aimed to interview residents who used and/or cultivated some native species. For morphometric analysis were recorded total height from the highest branch and the maximum number of stem ribs per plant, ground-level and chest level diameter. Managed and unmanaged plants were comparatively analyzed. Was created a distribution map with gathering and cultivation areas indicated by the residents through QGIS software. The Kruskal-Wallis test was applied to investigate the differences between the specimens managed and unmanaged, and the Pearson linear correlation test to test the correlation between the diameter x height. Results: People mentioned the management of six native species, through the collection, non-selective incipient management, and ex situ cultivation. Low complexity activities were the most frequent; also, there was little variation between the forms of management. Cereus jamacaru DC. was the most locally managed species and by a higher number of people, and it was observed that specimens from the Area of Direct Use (ADU) had greater variation. Conclusions: Intra-specific variants were identified by people and they said to prefer the larger and healthier branches and younger (green) cladodes, suggesting human selection that can favor particular phenotypes where these plants are propagated. Keywords: dry forest, ethnobotany, phenotypic variation, artificial selection